HUMAN RIGHTS VERSUS FUNDAMENTAL RIGHTS FOR ANIMALS: TOWARDS A NEW CATEGORY OF RIGHTS? - IYAMBA, Blaise Valentin; Augustin BEDIDJO ULAR, (IJRDO - Journal of Social Science and Humanities Research, 2019)
Human rights understood in its various senses open a new era in the 21st century to the questioning of the recognition of these same rights to non-human beings, including animals, although with specific legal protection at the international and national levels, do not have basic rights like human beings. The existing case law of the judicial decisions rendered in the United States, Argentina and India are eloquent to fuel the debate on the recognition of fundamental rights to animals. There is no doubt that animals do not have the capacity and the capacity to sue anyone, even against their counterparts for violation of any right. In this imbroglio, how can we recognize animals as holders of fundamental rights in the same way as human beings? This concern divides more than one researcher and constitutes the object of this work, which questions the probable future close to a new generation (4th generation of rights) and calls for a new legal engineering.